Are ploidy and age size-related? A comparative study on tetraploid Pleurodema kriegi and octoploid P. cordobae (Anura: Leptodactylidae) from Central Argentina - Otero, Manuel Alejandro (2017)
Size differences of anuran amphibian complexes with different ploidy levels are well known, whereas the larger species usually corresponds to a lower ploidy level. Neotropical Pleurodema kriegi (tetraploid) and P. cordobae (octoploid) differ in many morphometric variables and, in all cases, the species with the higher ploidy level corresponded to an increased body size. Although sexual size dimorphism (SSD) has been tested in P. kriegi without considering age-related differences in body size, SSD in P. cordobae is unknown. Here we determined individual age in order to analyse: (1) the intraspecific pattern of SSD of both species and (2) whether a larger body size and lower ploidy level relation observed in other polyploid anuran amphibians are reversed in a tetra-octoploid complex. Age and body size (snout-vent length) were correlated in both sexes and species. When the effect of age was controlled, significant a SSD were found. Intraspecific differences in demographic parameters were significantly higher than interspecific ones. We confirmed a female-biased SSD for both species and found the first case in which the larger species corresponds to a higher ploidy level. Different ploidy levels were an important factor determining age and body size under similar environmental conditions. Skeletochronology provided basic demographic data of P. kriegi and P. cordobae which are now available for comparative and conservation studies.